Impact of triglyceride glucose-weight adjusted waist index and its cumulative exposure on stroke risk: a nationwide prospective cohort study - Shiming He; Yinghao Kuang; Xinfang Huang; Yafei Jian; Jinyan Zhang; Wanfen Huang; Yang Zou; Guotai Sheng; Wei Wang; Hongyi Yang (Lipids in Health and Disease)
Abstract Background Insulin resistance and obesity are significant factors contributing to the incidence of stroke. The present research examines the association between stroke risk and both the triglyceride glucose-weight adjusted waist index (TyG-WWI, a composite marker of insulin resistance and obesity) and its cumulative exposure (CumTyG-WWI). Methods A total of 4,718 participants without baseline stroke history were included in this investigation, with new-onset stroke cases identified as the main study outcome. Cumulative exposure to the TyG-WWI was calculated based on repeated measurement data from the first and third waves of the national surveys. The relationships of TyG-WWI and CumTyG-WWI with stroke risk were examined using multivariable Cox regression, followed by validation in sensitivity analyses. Results Within a six-year median tracking period, 350 cases of stroke were documented among the research subjects. Following adjustment for confounding variables, the Cox regression analysis indicated progressively higher stroke risk with increasing TyG-WWI or CumTyG-WWI levels. Multiple sensitivity analyses further confirmed the robustness of these findings. Additionally, subgroup analysis results demonstrated significant differences in stroke risk associated with TyG-WWI and CumTyG-WWI across different age strata; specifically, individuals aged 45–59 years had a relatively higher stroke risk at similarly high levels of TyG-WWI and CumTyG-WWI compared to those aged ≥ 60 years. Conclusion Elevated baseline TyG-WWI was significantly associated with increased stroke risk. Moreover, the increasing cumulative exposure of TyG-WWI over time further elevates the risk of stroke occurrence. Graphic abstract